Metabolic profiling discriminates between strawberry (Fragaria × ananassa Duch.) cultivars grown in Finland or Estonia. (November 2016) - Kårlund, Anna; Moor, Ulvi; McDougall, Gordon; Lehtonen, Marko; Karjalainen, Reijo O.; Hanhineva, Kati
Abstract: Metabolic profiling analysis with LC-ESI-QTOF-MS was utilized to separate and identify 186 putative major metabolites demonstrating significantly different levels in 15 strawberry cultivars grown in Finland or Estonia. Principal component analysis showed close clustering of genetically related samples grown in Estonia, and hierarchical cluster analyses highlighted differences and similarities in their metabolic profiles driving separation between cultivars with specific metabolic phenotypes. Phenolic acids, flavonoids, flavan-3-ol derivatives, terpenes, and many types of glycosidically bound aroma and flavor precursors showed clear variation between strawberry cultivars. These cultivar-specific differences in the levels of major potentially bioactive phytochemicals in strawberries suggests that cultivar selection is essential for breeding strawberry cultivars with optimal phytochemical compositions contributing to possible functional properties and good cultivation and sensory qualities. Graphical abstract: Highlights: Strawberry cultivars were distinguished on the basis of their metabolic phenotypes. Genetically related strawberries showed resemblances in their metabolite profiles. Cultivar Jonsok contained high levels of potential aroma precursor compounds. Cultivar Polka was relatively rich in pelargonidin derivatives. Cultivar Rumba showed high levels of flavan-3-ol derivatives.